IoT technologies for elderly health care: a systematic mapping (Research, Society and Development, 2022)
Considering the challenges and benefits inherent to the Internet of Things (IoT) for the elderly in the health area, this study aimed to carry out systematic mapping of the literature, which the search was carried out in December 2021, in the Biblioteca Virtual em Saúde (BVS), Web of Science, Pubmed, Embase, and Medline databases. Some of the following descriptors were used: technology, application, health, Internet of Things and elderly. Were identified 873 studies and after applying the selection criteria, 39 publications reached the quality level for inclusion and inclusion. The reviewed articles present important data on the evolution of remote technological treatments for the elderly. This study is recommended to assist in research studies to increase knowledge, use, and quality of IoT technologies in health.